2013
DOI: 10.1016/j.geoforum.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Older people and outdoor environments: Pedestrian anxieties and barriers in the use of familiar and unfamiliar spaces

Abstract: A limited number of studies look at older people's use of space outside the 'home' environment, particularly unfamiliar, public urban space. Such unfamiliarity can be created through older people travelling as tourists to new areas; as a consequence of urban regeneration; or as a result of cognitive decline, where the familiar becomes unfamiliar. This paper explores the experiences of older people as pedestrians in unfamiliar urban spaces. In looks at two aspects: older people's spatial anxieties and the barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 38 publications
2
81
0
4
Order By: Relevance
“…Research has suggested that poor paving is a barrier for older people in engaging with outdoor environments [34]. However, in this case, while the paving quality may be poor in the green space compared with that of the urban busy and urban quiet spaces, the urban spaces have an increased need for increased vigilance due to road crossings, increased pedestrian and vehicular traffic and increased levels of noise, combining to create potential 'sensory overload'.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that poor paving is a barrier for older people in engaging with outdoor environments [34]. However, in this case, while the paving quality may be poor in the green space compared with that of the urban busy and urban quiet spaces, the urban spaces have an increased need for increased vigilance due to road crossings, increased pedestrian and vehicular traffic and increased levels of noise, combining to create potential 'sensory overload'.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults are generally found to be less efficient than young ones at determining the complex course of actions needed to reach the predefined goal; they make more mistakes and take more time to prepare the journey (Allain et al, 2005;Sander and Schmitter-Edgecombe, 2012). These findings are problematic, because before navigating to an unfamiliar place, older pedestrians often plan their journey on a map in order to reduce the risk of getting lost and the anxiety that ensues (Phillips et al, 2013). Age-related planning deficits are not as great, however, for more common tasks (e.g., Garden et al, 2001;Phillips et al, 2006), which are more similar to daily life situations in a familiar environment.…”
Section: Planning the Journeymentioning
confidence: 99%
“…The result of the cognition process is belief, which is defined as the cognition evaluation of affairs according to specific attributes or characteristics. Cognition is the temporary understanding, knowing, and opinions of a person to people or affairs (Phillips et al, 2013). Lu and Stepchenkova (2012) defined "cognition", with general explanations, as all forms of knowing, including feeling, memory, inference, perception, plan, notice, imagination, expectation, decision, problem-solving, and thought communication to further discuss the ecotourism cognition of visitors.…”
Section: Ecotourism Cognitionmentioning
confidence: 99%